2023
DOI: 10.1111/joa.13918
|View full text |Cite
|
Sign up to set email alerts
|

Cortical bone distribution of the proximal phalanges in great apes: implications for reconstructing manual behaviours

Abstract: Primate fingers are typically in direct contact with the environment during both locomotion and manipulation, and aspects of external phalangeal morphology are known to reflect differences in hand use. Since bone is a living tissue that can adapt in response to loading through life, the internal bone architecture of the manual phalanges should also reflect differences in manual behaviours. Here, we use the R package Morphomap to analyse high‐resolution microCT scans of hominid proximal phalanges of digits 2–5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
10
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(17 citation statements)
references
References 112 publications
3
10
2
Order By: Relevance
“…We expect to observe similar relative patterns and interspecific differences in cortical morphology of the intermediate phalanges that we did in the proximal phalanges (PPs) (Syeda et al, 2023). Specifically, we expect Pongo and H. sapiens to show similar patterns between their respective IPs and PPs, while African apes will show greater differences between their phalangeal elements due to direct loading of the IPs during knuckle-walking.…”
Section: Comparison Of Proximal and Intermediate Phalangesmentioning
confidence: 53%
See 4 more Smart Citations
“…We expect to observe similar relative patterns and interspecific differences in cortical morphology of the intermediate phalanges that we did in the proximal phalanges (PPs) (Syeda et al, 2023). Specifically, we expect Pongo and H. sapiens to show similar patterns between their respective IPs and PPs, while African apes will show greater differences between their phalangeal elements due to direct loading of the IPs during knuckle-walking.…”
Section: Comparison Of Proximal and Intermediate Phalangesmentioning
confidence: 53%
“…We previously explored cortical bone distribution patterns and properties in the proximal phalanges of digits 2-5 (PP2-PP5) in extant great apes and showed that the pattern of cortical bone within the non-pollical proximal phalanges is capable of distinguishing varied hand postures employed by each taxon and corresponds with predicted loading during these hand postures (Syeda et al, 2023). Results also indicated that cortical bone patterns and properties reflect the variable digital loading within the hand of each taxon (Syeda et al, 2023). Here, we build upon this research and provide the first detailed, comparative study of the cortical morphology of extant hominid intermediate phalanges in digits 2-5.…”
Section: Functional Morphology Of the Intermediate Phalangesmentioning
confidence: 99%
See 3 more Smart Citations